Multiple giant pancreatic pseudocysts, a rare complication of acute pancreatitis – A case report - Albail Singh Yadav,; Anant Agarwal,; Ayush Maurya,; Gaurang Agarwal, (Asian Journal of Medical Sciences, 2024)
A 34-year-old alcoholic male presented to our outpatient department with a complaint of persistent epigastric pain, radiating to the back with a swelling in the upper abdomen. He had 2 similar episodes in the past for which he was conservatively managed along the lines of acute pancreatitis. Now on physical examination, the patient had a massive lump in the upper abdomen reaching below the umbilicus. Examination findings were confirmed by computed tomography - abdomen (Plain and Contrast), two 13×10×09 cm and 9×8×7.8 cm, cystic lesions (Noncommunicating) were seen abutting the posterior wall of the stomach and into each other, suggestive of mature pseudocysts of the pancreas. The patient was admitted and after necessary investigations, surgical cystogastrostomy was done for the lower pseudocyst and cystocystostomy for the upper pseudocyst. The patient was discharged 5 days later with no complications. This case shows that multiple pseudocysts, a relatively rare complication of acute pancreatitis, are one of the differentials of acute abdomen. The treatment is a therapeutic challenge that depends on location, size, number as well as their relation to one another. Good drainage prevents resection procedures and further complications (exocrine and endocrine insufficiency).